The role of advertising campaigns in the Latin American integration process in Spain - Carcelén García, Sonia (2022)
Immigration has become a phenomenon with relevant social and economic consequences in Spain due to the increase of foreign populations in the last several years. This work focuses on studying different aspects that favour the immigrants’ integration in Spain and the role of advertising in this process. The methodological approach used is markedly qualitative based on social studies, content analysis and in-depth interviews with different professionals and focus-groups. The results of this study have shown that advertising contributes effectively to the integration process.